Bahasa Inggris - Murtadho, Raihan Akbar; Usdek Riyanto, Dicky Wisnu; Febriani, Rizki (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Workload, perceived organizational support, and job satisfaction play crucial roles in enhancing employees' work-life balance. The purpose of this study is to analyze the effects of workload and perceived organizational support on work-life balance, with job satisfaction as an intervening variable. This research using a quantitative method, using SmartPLS 4 and SPSS for data processing. Data were collected through online electronic questionnaires and interviews with several employees. The study involved 130 employees as population, selected using a stratified sampling method. Path analysis was utilized for data analysis. Workload has a significant negative effect on work-life balance. Perceived organizational support does not significantly influence work-life balance. Job satisfaction has a significant positive effect on work-life balance. Workload has a significant negative effect on job satisfaction. Perceived organizational support has a significant positive effect on job satisfaction. Job satisfaction mediates the impact of workload on work-life balance. Job satisfaction mediates the impact of perceived organizational support on work-life balance. The authors suggest that research on work-life balance can use variabels other than workload, perceived organizational support, and job satisfaction to reveal other contributions outside of these variables.